Fact-Checking en los debates electorales televisados de las elecciones generales de 2015 y 2016. - Mazaira-Castro, Andrés; Rúas-Araújo, José; Puentes-Rivera, Iván (Revista Latina de Comunicación Social, 2019)
Introduction: This article fact-checks the statements made in the televised debates that took place during the Spanish general elections of 2015, between Mariano Rajoy (PP) and Pedro Sánchez (PSOE), and 2016, between Soraya Sáenz de Santamaría (PP), Pedro Sánchez (PSOE), Albert Rivera (Ciudadanos) and Pablo Iglesias (Podemos). Methods: A total of 335 and 382 factual assertions were extracted from two thematic blocks of the 2015 and 2016 debates, respectively, and subsequently factchecked in order to determine their veracity. Results: More than 85% of the factual assertions made by participants were accurate. In fact, data accuracy was very high in the case of government representatives (95.4% in the case of Mariano Rajoy and 84.38% in the case of Soraya Sáenz de Santamaría), followed by Pablo Iglesias (92%), Albert Rivera (88.89%) and Pedro Sánchez (58.1% and 69.23% in the 2015 and 2016 debates, respectively). Discussion and conclusions: Participants in televised debates use a significant amount of factual assertions that reveal their more technical or political profiles. However, they hardly cite their sources, which complicates fact-checking by the audience.